Beneficial effects of green tea catechins on female reproductive disorders: a review - Mohd Kamal, Datu Agasi; Salamt, Norizam; Mohamad Zaid, Siti Sarah; Mokhtar, Mohd Helmy (Multidisciplinary Digital Publishing Institute, 2021)
Tea is one of the most widely consumed beverages worldwide after water, and green tea accounts for 20% of the total tea consumption. The health benefits of green tea are attributed to its natural antioxidants, namely, catechins, which are phenolic compounds with diverse beneficial effects on human health. The beneficial effects of green tea and its major bioactive component, (−)-epigallocatechin-3-gallate (EGCG), on health include high antioxidative, osteoprotective, neuroprotective, anti-cancer, anti-hyperlipidemia and anti-diabetic effects. However, the review of green tea’s benefits on female reproductive disorders, including polycystic ovary syndrome (PCOS), endometriosis and dysmenorrhea, remains scarce. Thus, this review summarises current knowledge on the beneficial effects of green tea catechins on selected female reproductive disorders. Green tea or its derivative, EGCG, improves endometriosis mainly through anti-angiogenic, anti-fibrotic, anti-proliferative and proapoptotic mechanisms. Moreover, green tea enhances ovulation and reduces cyst formation in PCOS while improving generalised hyperalgesia, and reduces plasma corticosterone levels and uterine contractility in dysmenorrhea. However, information on clinical trials is inadequate for translating excellent findings on green tea benefits in animal endometriosis models. Thus, future clinical intervention studies are needed to provide clear evidence of the green tea benefits with regard to these diseases.